Effect of glycaemic control and duration of disease on overnight albumin excretion in diabetic children. Issue 6450 (13th October 1984) - Rowe, D J; Hayward, M; Bagga, H; Betts, P
Abstract : Urine albumin excretion rates were measured in overnight timed samples from diabetic and non-diabetic schoolchildren. The excretion rates in the diabetics were significantly higher than those in the controls and were positively correlated with age, duration of diabetes, and glycaemic control. Diabetic children aged 12 years and older had significantly higher albumin excretion rates than younger diabetic children matched for duration of disease. Among the non-diabetic controls there was no correlation between albumin excretion rate and age and the girls excreted significantly more albumin than the boys. Measurement of the overnight albumin excretion rate may provide a useful early indicator of the progression to clinical proteinuria in diabetes and is free from random variations such as that due to exercise.